Constitutive expression of growth-related mRNAs in proliferating and nonproliferating lung epithelial cells in primary culture: evidence for growth-dependent translational control. - Clement, A (1990)
We describe the control of proliferation and growth-related gene expression in primary cultures of epithelial cells derived from rat lung. Type 2 epithelial cells line the gas-exchange surface of the alveoli where they produce and secrete surfactant. When isolated from adult animals, type 2 cells do not proliferate in culture, although they have a limited ability to do so in vivo. We show that type 2 cells isolated from neonatal rats proliferate in culture and that growth can be reversibly arrested by withdrawing serum from the medium. We studied the expression of five genes whose mRNA levels fluctuate with the state of proliferation in several cell systems: the c-myc and c-Ha-ras protooncogenes and the genes encoding actin, ornithine decarboxylase (L-ornithine carboxy-lyase, EC 4.1.1.17), and histone 3.2. All five mRNAs were constitutively expressed at identical levels in proliferating and nonproliferating (serum deprived) neonatal cells and in adult cells. Thus, at the level of mRNA abundance, the expression of these five genes was uncoupled from the growth state of the cells. By contrast, synthesis of the replication-dependent histones and the activity of ornithine decarboxylase were detectable only in proliferating neonatal cells and not in serum-deprived neonatal cells or in adult cells. The results suggest that, in type 2 cells, growth factors might regulate the translation, rather than the mRNA abundance, of at least some growth-related genes and that the ability to respond to this translational control may be developmentally regulated.